Peran Student Well-Being dan School Climate terhadap Prestasi Akademik pada Siswa SMP Yayasan “X” Bandung - Maria Yuni Megarini Cahyono; Trisa Genia Chrisantiana; Ellen Theresia (Universitas Kristen Maranatha, 2021)
This study aims to determine the role of student well-being and school climate on the academic achievements of